Gaming Capital on Overwatch's Official Forums - Korkeila Henry; Dashiell Steven; Harviainen J. Tuomas (SAGE PUBLICATIONS INC, 2025)
This study uses the public discussion boards of Overwatch to see how context-based gaming capital is present, accumulated and expended through the messages. The data consists of a 1-month snapshot from which 50 most viewed threads were analyzed. The following aspects were recorded from each thread and first 10 replies: views, number of comments, users' role in forums, has the developer replied to thread, topic, date, whether there are types of capital (social, economic, cultural, symbolic) present, and in what linguistic form is the message posted. Findings: while discussions are within Overwatch's framework, there is scarcely any demonstrable amount of gaming capital in a single post or reply. Certain topics elicited more discussion, articulation methods varied but greatly leaned on the user's anecdotal experiences. Further, it was found that gaming capital is used to validate users' own views and argument for the credibility of the user and their messages.